Evaluating Environmental Performance of Pulp and Paper Manufacturing Using the Analytic Hierarchy Process and Life‐Cycle Assessment - Ruby Pineda‐Henson; Alvin B. Culaba; Guillermo A. Mendoza (Journal of Industrial Ecology, 2002)
Summary This article addresses the need for a structured and compre‐hensive methodology for assessing the environmental perfor‐mance of manufacturing processes. The analytic hierarchy pro‐cess (AHP) is used as the basic framework for analyzing environmental impacts and improvement options following a streamlined life‐cycle assessment (LCA) approach that is fo‐cused on the manufacturing operation. The multicriteria de‐cision analysis approach of the AHP is consistent with the LCA concept because the environmental factors can be hierarchi‐cally structured into impacts and improvement options. Its po‐tential as a valuation tool for impact and improvement assess‐ment addresses both qualitative and quantitative issues in environmental decision making. Through application to a pulp and paper manufacturing case study, the viability of the AHP for evaluating environmen‐tal impacts and prioritizing process improvement options rela‐tive to these impacts is demonstrated. AHP was used to pro‐vide a quantitative tool for the design of a set of weighting factors for impact and improvement analyses.